Gavin & Stacey. Season two [videorecording (DVD)] - Corden, James; Jones, Ruth, 1966-; Page, Joanna, 1978- (Warner Home Video, 2008)
Returns for a second season of romance and more misunderstandings and run-ins between their hilarious families! Season Two finds Gavin and Stacey just returning from their honeymoon. The happy couple plans to live with Gavin's parents in Essex until they can get a place of their own. However, while Gavin won't even consider moving to Barry, Stacey feels bad for leaving her family and wants to be there to support her newly pregnant best friend Nessa.